PENDAPAT KEPALA SEKOLAH DAN GURU PAMONG TENTANG KOMPETENSI PEDAGOGIK MAHASISWA PLP PGPAUD - Mashfufah, Syifa Rohmati; Setiasih, Ocih; Eliyawati, Cucu (Prodi PGPAUD, 2016)
Principals and Mentor-Teachers’ Opinionson The Pedagogic Competence Of PGPAUD FIP UPI Students Taking Professional Internship Program Academic Year 2014-2015. The research aims to find the opinions of principals and mentor-teachers on the pedagogic competence of PGPAUD FIP UPI Students taking professional internship program in the academic year of 2014-2015. It adopted descriptive survey method. The population and sample of this research were all principals and mentor-teachers who supervised the professional internship program for 2014-2015 academic year. Data were collected using close-ended questionnaires as the instrument and were then analyzed with descriptive statistic.The principals’ opinion on the pedagogic competence of PGPAUDstudents taking professional internship program was good with a score of 72.93%. Mentor-teachers’ opinion on the pedagogic competence of PGPAUD students taking professional internship program was good as well with a score of 62.06%. The research recommends that the instructional strategies used in improving pedagogic competence be more applicative, especially for the strategies used in teaching instructional evaluation, so that in addition to being able to identify concepts of instructional evaluation, students can practice applying the techniques in the field. Future research is suggested to raise issues on pedagogic competence in the study program of Early Childhood Teacher Education in Indonesia to reveal further results and findings.The study program of Early Childhood Education is recommended to create more competent graduates of early childhood education teachers. Pendapat Kepala Sekolah dan Guru Pamong tentang Kompetensi Pedagogik Mahasiswa PLP PGPAUD FIP UPI Tahun Akademik 2014-2015. Tujuan penelitian ini adalah untuk mengetahui pendapat kepala sekolah dan guru pamong tentang kompetensi pedagogik mahasiswa PLP PGPAUD FIP UPI tahun akademik 2014-2015. Metode yang digunakan survei deskriptive. Populasi dan sampel pada penelitian ini adalah seluruh kepala sekolah dan guru pamong yang menjadi pembimbing program PLP tahun akademik 2014-2015. Alat pengumpulan data penelitian ini menggunakan angket tertutup yang kemudian dianalisis dengan statistika deskriptif. Kepala sekolah berpendapat tentang kompetensi pedagogik mahasiswa PLP PGPAUD adalah baik dengan nilai 72,93%. Pendapat guru pamang tentang kompetensi pedagogik mahasiswa PLP PGPAUD adalah baik dengan nilai 62,06%. Rekomendasi penelitian ini agar strategi pembelajaran yang digunakan dalam meningkatkan kompentensi pedagogik lebih aplikatif, khususnya untuk strategi pembelajaran matakuliah evaluasi pembelajaran, sehingga mahasiswa selain dibekali pengetahuan mengenai konsep-konsep evaluasi pembelajaran, mahasiswa juga dapat berlatih untuk menggunakan teknik-teknik penilaian di lapangan secara langsung. Untuk penelitian selanjutnya agar dapat mengangkat permasalahan mengenai kompetensi pedagogik pada program studi PGPAUD di Indonesia sehingga diharapkan peneliti mendapatkan temuan baru dan memberikan rekomendasi untuk program studi PGPAUD dan menghasilkan lulusan-lulusan guru PAUD yang lebih baik lagi.